2016
DOI: 10.21511/imfi.13(4).2016.09
|View full text |Cite
|
Sign up to set email alerts
|

Positioning firms in a new business performance space: an empirical study design on Euronext listed companies

Abstract: Purpose - This research was designed to shed light on what is the role played by intellectual capital within firms for the achievement of leadership positions, according to two main perspectives: (i) intellectual capital commitment and (ii) financial/market performances. Design/methodology/approach - An exploratory study design, involving 10-year data about 45 firms listed on Euronext 100, was devised. Firstly, firms were rated according to their intellectual capital commitment and their financial performances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In current market conditions, the statement that two key factors determine the choice of competitive strategy of the company remains relevant: the profitability of the industry and the positioning of the company within one or another industry [3,5]. Depending on the company's positioning relative to other market participants, its revenues will be higher or lower than the average level in the industry.…”
Section: The Genesis Of the Approaches To The Market Positioning Stramentioning
confidence: 99%
See 1 more Smart Citation
“…In current market conditions, the statement that two key factors determine the choice of competitive strategy of the company remains relevant: the profitability of the industry and the positioning of the company within one or another industry [3,5]. Depending on the company's positioning relative to other market participants, its revenues will be higher or lower than the average level in the industry.…”
Section: The Genesis Of the Approaches To The Market Positioning Stramentioning
confidence: 99%
“…In foreign and domestic scientific literature, some problems of price positioning of transnational corporations considered many authors [1][2][3][4][5][6][7][8][9][10]. In these works, the definitions of the key concepts of strategic management that form the basis of the positioning concept are given: 1) positioning related to the long-term strategy of the company since it takes time to create the desired position; 2) positioning occurring in the minds of consumers; 3) positioning based on obtaining the benefit; 4) the product's position in the mind of one buyer may differ from the same product's position in the mind of another buyer.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, external parties can also take advantage of the usefulness of this model and one of them is the credit risk analyst of a financial institution which lends money to companies for running their businesses. At present, the credit risk analyst adopts the established practice for the credit risk assessment of loan applicants by mainly making use of the financial reports (Iazzolino, Migliano, & Gregorace, 2013). However, any knowledge leakage can potentially affect the competitive advantage significantly, putting its earning capacity in doubt.…”
Section: Application Ii: Using the Model In Credit Risk Analysismentioning
confidence: 99%
“…Finally, this important numeric risk score can be fed into the credit risk analysis system of the lending company as part of the regular input data, making it a strong candidate to be one of the independent variable with the potential to enhance the credit risk analysis results. Earlier work by Iazzolino et al (2013) showed that the use of intellectual capital related data (knowledge leakage is in this category) can benefit credit risk analysis. Further modelling work on the credit risk analysis software is required to realise this perceived advantage of the model.…”
Section: Application Ii: Using the Model In Credit Risk Analysismentioning
confidence: 99%